Vestibular Aqueduct Morphology Correlates With Endolymphatic Sac Pathologies in Menière's Disease—A Correlative Histology and Computed Tomography Study. Issue 5 (June 2019) - Bächinger, David; Luu, Ngoc-Nhi; Kempfle, Judith S.; Barber, Samuel; Zürrer, Daniel; Lee, Daniel J.; Curtin, Hugh D.; Rauch, Steven D.; Nadol, Joseph B.; Adams, Joe C.; Eckhard, Andreas H.
Abstract : Hypothesis: The vestibular aqueduct (VA) in Menière's disease (MD) exhibits different angular trajectories depending on the presenting endolymphatic sac (ES) pathology, i.e., 1) ES hypoplasia or 2) ES degeneration. Background: Hypoplasia or degeneration of the ES was consistently found in inner ears affected by MD. The two etiologically distinct ES pathologies presumably represent two disease "endotypes, " which may be associated with different clinical traits ("phenotypes") of MD. Recognizing these endotypes in the clinical setting requires a diagnostic tool. Methods: 1) Defining the angular trajectory of the VA (ATVA) in the axial plane. 2) Measuring age-dependent normative data for the ATVA in postmortem temporal bone histology material from normal adults and fetuses. 3) Validating ATVA measurements from normative CT imaging data. 4) Correlating the ATVA with different ES pathologies in histological materials and CT imaging data from MD patients. Results: 1) The ATVA differed significantly between normal adults and MD cases with ES degeneration, as well as between fetuses and MD cases with ES hypoplasia; 2) a strong correlation between ATVA measurements in histological sections and CT imaging data was found; 3) a correlation between the ATVA, in particular its axial trajectory in the opercular region (angle α exit ), with degenerative ( α exit  < 120°) and hypoplastic ES pathology ( α exit  > 140°) was demonstrated. Conclusion: We established the ATVA as a radiographic surrogate marker for ES pathologies. CT-imaging-based determination of the ATVA enables endotyping of MD patients according to ES pathology. Future studies will apply this method to investigate whether ES endotypes distinguish clinically meaningful subgroups of MD patients. Abstract : Supplemental Digital Content is available in the text